Valuable carcasses: postmortem preservation of fatty acid composition in heart tissue. Issue 1 (20th February 2019) - Currie, Shannon E; Mène-Saffrané, Laurent; Fasel, Nicolas J
Abstract : Tissue degradation postmortem is an issue for the collection of representative biochemical data. We show that, for heart tissue, fatty acid composition is preserved up to 12-h postmortem. We advocate that carcasses may be a valuable resource in cases where euthanasia should be avoided because of ethical or conservation consideration. Abstract: In order to effectively conserve species, we must understand the structure and function of integral mechanisms at all levels of organismal organisation, from intracellular biochemistry to whole animal ecophysiology. The accuracy of biochemical analyses depend on the quality and integrity of the samples analysed. It is believed that tissue samples collected immediately postmortem provide the most reliable depiction of the living animal. Yet, euthanasia of threatened or protected species for the collection of tissue presents a number of ethical complications. Polyunsaturated fatty acids (PUFA) are essential to the cardiovascular system of all animals and the structure of PUFA can be degraded by peroxidation, potentially modifying the fatty acid composition of the tissue over postmortem time. Here, we assessed the composition of PUFA in cardiac tissue of bats ( Carollia perspicillata ) over the course of 12-h postmortem. We show that PUFA are resistant to naturally occurring postmortem degradation in heart tissue, with no difference in the overall composition of fatty acids across all time classes (0, 3, 6 or 12-h postmortem). Our results suggest that carcasses that would otherwise be discarded may actually be viable for the assessment of fatty acid composition in a number of tissues. We hope to spur further investigations into the viability of carcasses for other biochemical analyses as they may be an untapped resource available to biologists.